Rescate de los valores culturales como sentimiento nacional y cohesión social y generación de espacios de turismo en el Gobierno Autónomo Descentralizado Municipal del cantón Quinsaloma, 2014 - Unda Galeas, Marixa Lourdes (2015)
This research was conducted in the Decentralized Autonomous Municipal Government of the canton Quinsaloma, the same that is located northwest of the Province de los Rios. Its development began with an introduction, whose overall objective is: To rescue the cultural values and national sentiment and social cohesion and creation of opportunities for tourism in the Decentralized Autonomous Municipal Government of Quinsaloma Canton province of Los Rios; specific objectives) An analysis of the current situation of cultures and traditions in the canton Quinsaloma, b) determine the factors that allow for the creation of opportunities for tourism thanks to social cohesion in the canton Quinsaloma, c) Design a strategy to strengthen the rescue of cultural values and national sentiment in the tourism sector of the canton Quinsaloma. Necessary theoretical and legal foundations were integrated; the location Decentralized Autonomous Municipal Government of the canton Quinsaloma, materials and methods, applied research techniques was determined, the population of the canton Quinsaloma projected year 2014 in 17695 habitants, applying 376 surveys, and interview the Mayor of Municipal GAD. The objectives were developed. Surveys and interviews provided information required for analysis of the current situation of cultures and traditions in the canton Quinsaloma, proceeded to examine the factors that enable the creation of opportunities for tourism and proper strategies to strengthen the rescue cultural values and national sentiment in the tourism sector of the canton Quinsaloma. In conclusion the Canton Municipal GAD Quinsaloma not have an office that promotes tourism, tending to the rescue of cultural and traditional values of the area, to which the strategic proposal to rescue the beliefs currently recommend detected traditions and heritage. The literature survey was conducted in texts supplied by the library UTEQ, and Municipal GAD also consultations via the Internet. Instruments used as evidence and photographs taken at the scene are integrated.